1997
DOI: 10.5326/15473317-33-2-177
|View full text |Cite
|
Sign up to set email alerts
|

Gracilis or semitendinosus myopathy in 18 dogs

Abstract: The clinical findings in 18 dogs with gracilis (n = 17) or semitendinosus (n = 1) myopathy are described. Each dog had a similar hind-limb gait abnormality characterized by a shortened stride with a rapid, elastic medial rotation of the paw, internal rotation of the hock and external rotation of the calcaneus [corrected] and internal rotation of the stifle during the mid-to-late swing phase of the stride. Medical management prior to or in lieu of surgery was attempted (n = 8) with no apparent response. Fifteen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 0 publications
1
35
0
2
Order By: Relevance
“…We likewise had a good outcome at 15 and 30 days, but at 12 months, there was reunion of the sartorius tendon and onset of gracilis contracture. Others have reported recurrence of gracilis and semitendinosus myopathy 5 or 6 months after surgery 1,3,4 . Review of ultrasonography images in our dog revealed no presurgical evidence of gracilis myopathy.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…We likewise had a good outcome at 15 and 30 days, but at 12 months, there was reunion of the sartorius tendon and onset of gracilis contracture. Others have reported recurrence of gracilis and semitendinosus myopathy 5 or 6 months after surgery 1,3,4 . Review of ultrasonography images in our dog revealed no presurgical evidence of gracilis myopathy.…”
Section: Discussionsupporting
confidence: 48%
“…Sarli and colleagues reporting gracilis muscle myopathy in German Shepherds found that plasma concentrations of enzymes considered indicative of muscle damage (e.g., CK, LDH) were often within normal reference intervals. 4,11,12 Results of electromyographic examinations of gracilis myopathy have been variable, and Sarli and colleagues suggest that this reflects different phases of the same disease. 4,11,12 Magnetic resonance imaging may prove to be the best method of imaging myopathy 13 but was not performed in our dog.…”
Section: Discussionmentioning
confidence: 99%
“…Hematomas associated with partial muscle tears or blunt trauma are hypoechoic relative to surrounding tissues [17][18][19][20][21][22]. Normal muscle architecture is usually lost, but with time, normal structures generally return with healing.…”
Section: Allison Zwingenberger • Livia Benigni • Christopher R Lambmentioning
confidence: 99%
“…The condition may or may not be symmetrical. Myotomy or myectomy results in an immediate improvement, but is not advised, as all cases present again within one to five months of surgery due to the recurrence of fibrous tissue in the wound (Lewis and others 1997). The aetiology is unknown.…”
Section: Conditions Affecting the Hindlimbmentioning
confidence: 99%